THE IMPACT OF BREBES-TEGAL TOLL ROAD CONSTRUCTION ON LOCAL TRAFFIC CONDITIONS - Nafisah, Hasna (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
The construction of the Brebes-Tegal Toll Road is expected to improve transportation connectivity and economic efficiency in the region. This new infrastructure project aims to ease travel between major urban centers, facilitate trade, and reduce travel time for commuters. However, the new infrastructure may also impact local traffic conditions and accident rates in surrounding areas. This study investigates these effects, providing insight into potential benefits and challenges for local transportation systems. The study aims to analyze the impact of the Brebes-Tegal Toll Road construction on local traffic flow and accident rates in the surrounding areas. Specifically, it seeks to determine whether the construction improves or worsens traffic conditions and if there are significant changes in accident rates. To achieve this goal, this research uses a qualitative approach through a Likert scale questionnaire distributed to gather data on local residents' perceptions of traffic changes and safety. Respondents rated their observations on traffic flow, congestion, and accident frequency before and after the toll road construction. The study surveyed a sample of 113 respondents drawn from the local population in areas surrounding the Brebes-Tegal Toll Road. The respondents include cadets of PKTJ, regular road users, residents, and local business operators who experience the effects of the toll road in their daily activities. The findings indicate that while the Brebes-Tegal Toll Road has moderately improved traffic flow by reducing congestion on local roads, there is also a reported increase in accident rates near toll road access points. Respondents noted enhanced road quality and speed of travel on the toll road itself, yet some areas experienced higher accidents risks, likely due to increased vehicle volume and changes in traffic patterns. To mitigate the increased accident rates, it is recommended that traffic safety measures be implemented, such as better road signage, speed management near toll entrances, and public education campaigns on road safety in high-risk areas. Further collaboration with local authorities can enhance traffic flow and minimize accidents.